Drugost in vprašanje avtoritete - Hart, Jonathan Locke (Primerjalna književnost, 2009)
Comparisons among cultures open up new perspectives. This paper is a comparative discussion of western Europeans and how they came to terms with the otherness of Natives in the New World and how that called into question their own authority as authors and indeed their worldview. This representation of the Natives is a recurrent theme. Often this representation and "translation" involved an overcoming of or coming to terms with other "barbarous" cultures as well as an inheritance from a previous empire or a rival. Questions of being there, of the rhetorical contract between writer and reader, and the typology of the Old and New World are among my concerns over the truth and lies that the authors and readers of travel accounts must negotiate. This might be an ethnology of reading or a use of ethnology to see the otherness within or the dramatic tension between self and other that writers and readers then and now experience.
Keywords: književnost; literature; ideologija; zahodna kultura; ameriški staroselci; kulturni imperializem; drugost